Neurosurgical diseases an evidence-based approach to guide practice - Lai, Leon T.; Gragnaniello, Cristian (Thieme, 2022)
"Evidence-based neurosurgery is one of the most important pillars upon which to build decision management pathways. Effective delivery of care involves understanding the natural history of the disease and the evidence behind available treatment options. Neurosurgical Diseases: An Evidence-Based Approach to Guide Practice by esteemed neurosurgeons Leon T. Lai, Cristian Gragnaniello, and expert contributors covers cranial pathologies neurosurgeons commonly encounter in everyday practice"--